Peningkatan kemampuan komunikasi matematik peserta didik yang menggunakan model creative problem solving (CPS) - Vepi Apiati; Aei Fatimah (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2017)
Mathematical communication skills of learners are one of the achievements of the curriculum that must be possessed by learners in math learning. This study aims to determine the improvement of mathematical communication skills of better learners who use Creative Problem Solving (CPS) model by using direct learning model. Creative Problem solving (CPS) model is used as a learning model in this research to improve students' mathematical communication ability. Creative Problem Solving (CPS) model builds learners more active, creative and skilled in solving problems compared to direct learning models. The research was conducted on the students of class VIII SMP Negeri 4 Kota Tasikmalaya on the material to build the space side of flat by using experimental research method. Two classes were taken as samples, experiment class using Creative Problem Solving (CPS) model and control class using direct learning. Data collection techniques used in the form of test students' mathematical communication skills through pre test and post-test by using statistical analysis of normalized gain. The result of improvement of mathematic communication ability of students using Creative Problem Solving (CPS) model is better than using direct learning model.